Penyuluhan Pembuatan Media Pembelajaran Kepada Guru-Guru Pendidikan Yayasan Sulaimaniyah Kutacane - Khairuddin Nasution; Iswandi Walad; Fitra Jaya; Rahmadi Pandi Wijaya (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Learning media is one of the tools that is really needed by Sulaimaniyah Kutacane Foundation Education Teachers when teachers carry out their learning, both inside and outside the classroom. The use of learning media so far has only relied on manufactured learning media and not the work of teachers. These manufactured learning media are quite expensive and not affordable for the Sulaimaniyah Kutacane Foundation Education Teachers in the area. Likewise with the Sulaimaniyah Kutacane Foundation Education Teachers where community service is carried out. The method used in this community service is community education. the extension team carries out counseling, the extension team observes changes in the behavior of the Sulaimaniyah Kutacane Foundation Education Teachers, the extension team observes these changes in behavior and it is hoped that they can be applied to real actions that have a direct effect on the quality of learning, the extension team periodically observes the improvement in the quality of teachers' learning. Sulaimaniyah Kutacane Foundation Education teacher, the extension team observed the results of the extension that had been carried out, with the hope that teachers would become more skilled in creating their own learning media. The success of this community service activity, when seen from the Sulaimaniyah Kutacane Foundation Education Teachers, can reach 95%, because the Sulaimaniyah Kutacane Foundation Education Teachers who were given counseling were able to produce learning media products in accordance with what was explained by the extension team. The participation of the Sulaimaniyah Kutacane Foundation Education Teachers in this extension activity was complete and complete until the end of the activity. Extension activities for Sulaimaniyah Kutacane Foundation Education Teachers with other materials are suitable to be carried out next.